A Call for Quotas and Increased Transparency in the Academic Hiring Process (KULT_online, 2009)
From authors Christine Färber and Ulrike Spangenberg, this volume is an empirical analysis of equal opportunity as it pertains to the academic hiring process. The current state of the process, in general, and equal opportunity reforms, in particular, are revealed through qualitative interviews with hiring committee members, equal opportunity commissioners, and the applicants themselves. Nine interacting facets are observed and evaluated for their effects on equality in the workplace, and the legal foundation of equal opportunity hiring procedures is summarised by way of documentary research. Commission participants and other university employees should find the included checklists and summaries to be of much practical value. The authors consider the academic hiring process incapable of reforming itself independently, and therefore conclude that legally enforced quotas and other systemic changes are necessary.